Research progress on the utilization technology of broccoli stalk, leaf resources, and the mechanism of action of its bioactive substances - Yan, Lu; Zhou, Gang; Shahzad, Khuram; Zhang, Haoran; Yu, Xiang; Wang, Yusu; Yang, Nan; Wang, Mengzhi; Zhang, Xin (Frontiers in Plant Science, 2023)
Broccoli is a nutritious vegetable. It is high in protein, minerals, and vitamins. Also, it possesses antioxidant activities and is beneficial to the human body. Due to its active effect, broccoli is widely accepted by people in daily life. However, in terms of current utilization, only its florets are consumed as vegetables, while more than half of its stalks and leaves are not utilized. The stalks and leaves contain not only nutrients but also bioactive substances with physiologically regulating properties. Therefore research into the action and mechanism of its bioactive substances as well as its development and utilization technology will make contributions to the further promotion of its resource development and utilization. As a theoretical foundation for the resource utilization of broccoli stalks and leaves, this report will review the distribution and consumption of broccoli germplasm resources, the mechanism of action of bioactive substances, and innovative methods for their exploitation.